2020
DOI: 10.1177/0192513x19894351
|View full text |Cite
|
Sign up to set email alerts
|

“When I Iron My Son’s Shirt, I Feel My Maternal Role”: Making Women’s Invisible Work Visible

Abstract: This article seeks to learn how women perceive invisible work and how it affects their lives. This article contributes to the integration of different manifestations of invisible work into a conceptual whole, especially in light of the fact that most research has confined itself to only one aspect such as care work, housework, or volunteering. Nine group interviews were conducted with Israeli mothers from differing ethnic, religious, class, and age groups. Analysis reveals that the distinctions between aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Office housework consists of several types of tasks: literal housework, such as planning parties or cleaning up after a meeting; administrative work, such as taking notes; and emotional work (Williams et al., 2016). Others have found that, regardless of their accomplishments and formal position in the organizational hierarchy, women in caring occupations (Kaplan et al., 2020), women engineers (Williams et al., 2016), and women in universities (Babcock et al., 2017; El‐Alayli et al., 2018; Guarino & Borden, 2017) are expected to do more—and indeed do more—than men in regard to all types of unpaid work.…”
Section: Gendered Organizations and Invisible Work At Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Office housework consists of several types of tasks: literal housework, such as planning parties or cleaning up after a meeting; administrative work, such as taking notes; and emotional work (Williams et al., 2016). Others have found that, regardless of their accomplishments and formal position in the organizational hierarchy, women in caring occupations (Kaplan et al., 2020), women engineers (Williams et al., 2016), and women in universities (Babcock et al., 2017; El‐Alayli et al., 2018; Guarino & Borden, 2017) are expected to do more—and indeed do more—than men in regard to all types of unpaid work.…”
Section: Gendered Organizations and Invisible Work At Workmentioning
confidence: 99%
“…Recently, increasing efforts have been invested in studying invisible work in the labor market (Hatton, 2017; Kaplan et al., 2020). Studies have framed such practices as various aspects of unpaid work in the labor force (Baines, 2004; Baines et al., 2017; Hatton, 2017; C. Williams & Nadin, 2012; J. Williams & Dempsey, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While visibility is complex concept, engaging multiple multi-directional stakeholders (Kaplan et al., 2020), (in)visible work must have a potential observer for whom the work is rendered invisible or visible. In almost every conceivable case, the worker will observe and acknowledge that they are working, that they are engaging in an act of production, even if they cannot see the end results of their labour.…”
Section: Organisational Secrecy and Invisible Workmentioning
confidence: 99%
“…During the last 4 years, we conducted four group interviews with 32 women, in polygamous and non-polygamous relationships, asking them about their lives, about their relationships, and about the topics of divorce and polygamy. The setting of group interviews is seen as uniquely suitable for facilitating critical feminist epistemologies in that group interviews can promote diverse forms of expressions of women's insights and the shared, co-construction of knowledge (Kook et al, 2019;Kaplan et al, 2020). The interviews were conducted with 32 women divided into four groups, each group including eight adult women, with an age range chosen to represent different generations -that is, from 21 years of age to 60 years old.…”
Section: Interviewsmentioning
confidence: 99%